Early urine output monitoring in very preterm infants to predict in-hospital neonatal outcomes: a bicentric retrospective cohort study. Issue 1 (27th January 2023) - De Mul, Aurélie; Heneau, Alice; Biran, Valérie; Wilhelm-Bals, Alexandra; Parvex, Paloma; Poncet, Antoine; Saint-Faust, Marie; Baud, Olivier
Abstract : Objective: To evaluate whether urine output (UO), rarely assessed in the literature, is associated with relevant neonatal outcomes in very preterm infants, and which UO threshold may be the most clinically relevant. Design: Retrospective cohort study. Setting: Two Level IV neonatal intensive care units. Patients: Very preterm infants born between 24 0/7 and 29 6/7 weeks of gestation documented with eight UO measurements per day between postnatal day 1 and day 7. Main outcome measures: Composite outcome defined as death before discharge, or moderate to severe bronchopulmonary dysplasia, or severe brain lesions. The association between this outcome and UO was studied using several UO thresholds. Results: Among 532 infants studied, UO <1.0 mL/kg/hour for at least 24 consecutive hours was measured in 55/532 (10%) infants and the primary outcome was recorded in 25 patients. The association between a UO threshold <1.0 mL/kg/hour and the primary outcome was found marginally significant (crude OR 1.80, 95% CI 1.02 to 3.16, p=0.04). The primary outcome was recorded in 112/242 (46%) patients with a UO <2.0 mL/kg/hour and only 64/290 (22%) patients with a UO ≥2.0 mL/kg/hour (p<0.001). This UO threshold was found significantly associated with the primary outcome (crude OR 3.1, 95% CI 2.1 to 4.7, p<0.001), an association confirmed using a multivariate logistic regression model including baseline covariates (adjusted OR 3.7, 95% CI 2.2 to 6.4, p<0.001). Conclusion: A UO <2 mL/kg/hour over 24 hours between postnatal day 1 and day 7 strongly predicts neonatal mortality or severe morbidities in very preterm infants.